Comparative study between sequential use of Foley catheter with vaginal misoprostol versus sequential use of oral mifepristone with vaginal misoprostol for second trimester medical abortion - Fonseca, Michelle N.; Sah, Vernica (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Abortions are one of the most commonly performed procedures in gynaecological departments worldwide. They are still a major problem in developing countries contributing to a significant percentage of maternal morbidity and mortality. The main objective of this study is to compare the efficacy, side effects and acceptability of intracervical Foley and oral Mifepristone both followed with sequential administration of vaginal misoprostol for second trimester medical abortion. Methods: This was a prospective randomized trial of 36 healthy women opting for termination of pregnancy with ultrasound confirmed intrauterine gestation between 12 to 20 completed weeks. Intracervical Foley catheter with administration of misoprostol (200µg) vaginally was done for Group A. Mifepristone 200mg was administered on day one followed by misoprostol (200µg) vaginally, 48 hours later, to Group B. Both groups received misoprostol (200µg) vaginally at 4 hourly intervals. Completeness of abortion was assessed, and surgical evacuation was performed, if abortion was found to be incomplete. Results: The two groups were comparable with respect to age, parity and gestational age. 83-89% of the women in both the groups had complete abortion. The mean induction abortion interval was 20.11 hours in Group A and 54.77 hours in Group B, which was statistically significant. Side effect profile was comparable in both groups however the intensity and the duration of persistence of pain was greater among patients from Group A. Conclusions: Authors conclude that medical abortions with both methods were found to be safe, effective, inexpensive and acceptable methods. Whereas a shorter induction abortion interval was observed in the Foley induction group, induction with mifepristone was the preferred regimen in second trimester abortion because of its high efficacy, low incidence of side effects, better tolerance by the patients and due to lower dose of misoprostol required following mifepristone administration.